THE WEST AND THE CAPE SEA ROUTE - Dorning, W.A. (Scientia Militaria - South African Journal of Military Studies, 2012)
Changing perceptions and realities Western strategists and politicians have traditionally acknowledged the vital importance of the Cape Sea Route. Their South African counterparts, for their part, have in the past regarded the Cape Sea Route’s importance to the West as almost axiomatic, and have frequently sought to use this fact as a bargaining point in their negotiations with the Western Powers.1 There are increasing signs, however, that are-assessment of the importance of the Cape Sea Route is taking place in the West.